Where are they now? An analysis of integrated cardiothoracic surgery residency applicants - Christopher M. Worrell, MD; Nitin A. Das, MD; Edward Y. Sako, MD PhD (Surgery Open Science, 2024)
Changes in cardiothoracic surgery (CTS) workforce trends have affected training paradigms to include the establishment of integrated six-year CTS residency (I6) programs. This study aimed to determine commitment of selected I6 program applicants to the specialty.Internal archives at a single institution were accessed to identify applicants interviewed for an I6 position from 2014 to 2016. A systematic internet search of publicly available information was performed to identify the trainee's current specialty. Descriptive analysis was performed.Forty-seven applicants were identified. Successful search results were achieved for 97.9 % of the applicants. One applicant was excluded, resulting in a cohort of 45. 48.9 % of the applicants successfully matched into I6 programs. Of the 23 who did not match into an I6 program, 91.3 % began a General Surgery (GS) residency. When looking solely at the GS trainees, 71.4 % sought and matched into a traditional or 4/3 CTS residency. In total, 77.8 % of the cohort are currently pursuing careers in cardiothoracic surgery.The study identified a strong continued interest in the field of CT Surgery among those interviewed for integrated residency. The methodology used in this study provided an effective way to follow career choice of applicants interviewed and could be applied by additional programs to further elucidate career choice and levels of commitment.